Associations of urinary carbon disulfide metabolite with oxidative stress, plasma glucose and risk of diabetes among urban adults in China. (1st March 2021) - Xu, Tao; Wang, Bin; Wang, Xing; Yang, Shijie; Cao, Limin; Qiu, Weihong; Cheng, Man; Liu, Wei; Yu, Linling; Zhou, Min; Wang, Dongming; Ma, Jixuan; et al.
Abstract: Carbon disulfide (CS2 ) has been reported to induce disorder of glucose metabolism. However, the associations of CS2 exposure with plasma glucose levels and risk of diabetes have not been explored in general population, and the underlying mechanisms remain unclear. We aim to examine the relationships between CS2 exposure and fasting plasma glucose (FPG) levels, as well as diabetes, and assess the potential role of oxidative stress among the abovementioned relationships in Chinese general adults. The concentrations of urinary biomarkers of CS2 exposure (2-thiothiazolidin-4-carboxylic acid, TTCA), and biomarkers for lipid peroxidation (8-isoprostane, 8-iso-PGF2α ) and DNA oxidative damage (8-oxo-7, 8-dihydro-20-deoxyguanosine, 8-OHdG) were measured among 3338 urban adults from the Wuhan-Zhuhai cohort. Additionally, FPG levels were tested promptly. Generalized linear models and logistic regression models were used to quantify the associations among urinary TTCA, oxidative damage markers, FPG levels and diabetes risk. Mediation analysis was employed to estimate the role of oxidative damage markers in the association between urinary TTCA and FPG levels. We discovered a significant relationship between urinary TTCA and FPG levels with regression coefficient of 0.080 (95% CI: 0.002, 0.157). Besides, the risk of diabetes was positively related to urinary TTCA (OR:1.282, 95% CI: 1.055, 1.558), particularly among those who did not exercise regularly. Each 1% increase of urinary TTCA concentration was associated with a 0.096% and 0.037% increase in urinary 8-iso-PGF2α and 8-OHdG, respectively. Moreover, we found an upward trend of FPG level as urinary 8-iso-PGF2α gradually increased ( P trend <0.05), and urinary 8-iso-PGF2α mediated 21.12% of the urinary TTCA-associated FPG increment. Our findings indicated that urinary CS2 metabolite was associated with increased FPG levels and diabetes risk in general population. Lipid peroxidation partly mediated the association of urinary CS2 metabolite with FPG levels. Graphical abstract: Image 1 Highlights: Urinary CS2 metabolite was associated with elevated 8-iso-PGF2α, 8-OHdG, FPG levels and diabetes in general population. We found linear dose-response relationships of urinary CS2 metabolite with 8-iso-PGF2α, and urinary 8-iso-PGF2α with FPG. Urinary 8-iso-PGF2α mediated 21.12% of the urinary TTCA-associated FPG increment. Abstract : Urinary CS2 metabolite was associated with increased FPG levels and diabetes risk, and lipid peroxidation partly mediated the relationship between urinary CS2 metabolite and FPG levels.